Altruism & altruistic love science, philosophy, & religion in dialogue - Post, Stephen Garrard, 1951- (New York ; Oxford : Oxford University Press, 2002)
This text examines evolutionary, neurological, psychological social, cultural and religious aspects of altruistic behaviour. It presents an overview, a review of contemporary research, and various debates, as well as possible future directions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Altruism